Influence Pre-Treatment On The Properties Of Lignocellulose Based Biocomposite - S.S, Suradi; R. M., Yunus (2009)
Natural fibers are gaining progressive account as a renewable, environmentally acceptable, and biodegradable reinforcing fibre which combine acceptable mechanical properties with a low density. The utilization of biomass (lignocelluloses) for the processing of novel composites has attracted growing interest because of its eco-friendly and renewable nature. The major challenge for natural fibre composites is their inherent poor adhesion between fibre and the matrix. In this study the lignocelluloses were treated with alkaline peroxide to remove lignin. Treatment time, temperature and concentration were optimized on the basis of removal of noncellulosic compound. The non-cellulose and celluloses fibres were blended in different ratios up to 50 wt% with polypropylene (PP) matrix using Twin-screw extruder. Samples were prepared by using injection molding machine and tested using tensile, flexural and impact tester. It was found that the mechanical properties were improved by the alkaline peroxide treatment of fibre. Also, elimination of lignin contents of fibre strongly influenced on the properties of polypropylene composite which was evaluated by using Scanning Electron Microscope (SEM) and Fourier Transform Infrared Spectrophotometry (FTIR).